Exploring the Implementation of Project-Based Learning in Primary English Classrooms: Insights from Teachers’ and Students’ Perspectives - Ni Made Arini Sasmita; Luh Putu Artini; Putu Suarcaya (EDUJAVARE: International Journal of Educational Research, 2026)
The implementation of Project-Based Learning (PjBL) in primary English classrooms is important to investigate because it enhances students’ motivation and engagement despite challenges in instructional practices and assessment. This study aims to explore the implementation of Project-Based Learning (PjBL) in primary English classrooms, focusing on planning, implementation, assessment, and the perceptions of teachers and students. This research employed a qualitative approach with a case study design conducted at Bali Kiddy Primary School. The participants consisted of English teachers and fifth-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, documentation, and self-reflection journals, and analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings reveal that PjBL has been implemented with several strengths, particularly in enhancing student motivation, engagement, collaboration, and confidence in using English. Students actively participated in group work and showed positive attitudes toward learning through projects. However, several challenges were identified, including limited alignment in lesson planning, unclear instructional guidance, time constraints, and assessment practices that focus more on final products rather than learning processes. Project-Based Learning has strong potential to improve English learning at the primary level by creating meaningful and student-centered learning experiences. Nevertheless, improvements in planning, instructional clarity, and comprehensive assessment strategies are necessary to optimize its implementation